Student Penmanship as Predictors of Test scores Among Form One students in Dadaab Refugee Camp, Kenya. - Surum, Janet; Okatcha, Frederick; Koinange, Chrispus (IJRDO- Journal of Educational Research, 2016)
The Kenya National Examinations are a great determinant of the success and failure in the future life of Kenyan students. Due to this, the pressure to perform has been overwhelming for most learners. Students can go to any length to see to it that they make it. The purpose of the study therefore was to determine the relationship between   student penmanship   and test scores among form ones students in Dadaab Refugee Camp, Kenya. The study was guided by the following   theory: Social cognitive learning by Albert Bandura. The study adopted a correlational design in order to be able to investigate and analyze the relationship between   student penmanship and form one test scores. It also used simple regression to find out whether the various variables would predict test scores. The study was conducted in four public schools of Dadaab refugee camps in the North-Eastern part of Kenya. The target population consisted of students and teachers. The sampling technique was that of convenient, purposive and systematic sampling in that order, where thirty five participants were selected from each school, to sum up to one hundred and thirty eight form one students and a total of thirty four teachers. Research instruments included questionnaires for teachers and students, while interview schedule was for teachers. The results revealed that student penmanship do not significantly predict test scores.